Diet quality and physical activity affect metabolic dysfunction-associated steatotic liver disease, metabolic dysfunction and etiology-associated steatohepatitis, and compensated advanced chronic liver disease among United States adults: NHANES 2017–2020 - Wang, Peng; Xia, Bingxin; Wang, Shuang (Frontiers in Nutrition, 2025)
Background and aimClinical data on the prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) and metabolic dysfunction and etiology-associated steatohepatitis (MetALD) in a multi-ethnic U.S. population are limited. Additionally, the impact of physical activity (PA) and diet quality (DQ) on the risk of MASLD, MetALD, and compensated advanced chronic liver disease (cACLD) remains unclear. This study aimed to investigate the associations of PA and diet quality with the risks of MASLD, MetALD, and cACLD.Methods and resultsThis cross-sectional study analyzed data from 7,125 participants in the National Health and Nutrition Examination Survey (NHANES) 2017–2020. Diet quality was assessed using the Healthy Eating Index-2015 (HEI-2015). PA was assessed based on the 2020 WHO Physical Activity Guidelines, with participants reporting the intensity, frequency, and duration of their activities over the past 7 days. MASLD and MetALD were diagnosed based on clinical criteria, and cACLD was defined by advanced liver fibrosis. Bivariate and multivariable logistic regression models were used to assess associations between PA, diet quality, and liver disease outcomes. The prevalence of MASLD and MetALD was 35.07 and 21.46%, respectively. HQD was associated with significantly lower risks of MASLD (OR: 0.49, 95% CI: 0.38–0.62) and MetALD (OR: 0.45, 95% CI: 0.36–0.56). High PA levels were linked to reduced risks of MASLD (OR: 0.47, 95% CI: 0.38–0.58) and MetALD (OR: 0.53, 95% CI: 0.39–0.72). The lowest risks for both MASLD and MetALD were observed in highly active participants with an HQD (MASLD OR: 0.41, 95% CI: 0.32–0.53; MetALD OR: 0.54, 95% CI: 0.41–0.71). Significant interactions were observed between PA, HQD, and age, BMI, and SES, which further reduced the risks of MASLD and MetALD. For cACLD, both increased PA and HQD were associated with reduced risk. Compared to non-high-activity participants with a non-HQD, physically active participants with an HQD had the lowest risk of cACLD (OR: 0.44, 95% CI: 0.24–0.82).ConclusionHigh proportions of the US population have MASLD or MetALD. HQD and high PA levels were associated with lower risks of MASLD, MetALD, and cACLD.